The Effects of Electronic Cigarette (ECIG)-Generated Aerosol and Conventional Cigarette Smoke on the Mucociliary Transport Velocity (MTV) Using the Bullfrog (R. catesbiana) Palate Paradigm - Palazzolo, Dominic L.; Nelson, John M.; Ely, Emily A.; Crow, Andrew P.; Distin, James; Kunigelis, Stan C. (Frontiers in Physiology, 2017)
Background: While ECIGs are under scrutiny concerning safety, particularly in reference to the physiological impact that aerosolized ECIG liquid (E-liquid) may have on respiratory tissues, others believe that ECIGs are a “Harm Reduction” alternative to conventional cigarettes. Previous studies investigating ciliated respiratory epithelium indicate that smoking shortens cilia length, reduces cilia beat frequency and disrupts respiratory epithelium, which most likely contributes to the inhibition of mucocilliary clearance. Monitoring mucous clearance of respiratory tissues exposed to ECIG-generated aerosol or conventional cigarette smoke, as indexed by mucous transport velocity (MTV), is one way to gauge the impact aerosol and smoke have on the respiratory tract. Therefore, we designed an experiment to test the effect of ECIG-generated aerosol and smoke on MTV using the frog palate paradigm. Methods: Peristaltic pumps transport ECIG-generated aerosol and conventional cigarette smoke into custom-made chambers containing excised bullfrog palates. MTVs were determined before exposure, immediately after exposure and approximately one day following exposure. MTVs were also determined (at the same time points) for palates exposed to air (control). Surface and cross sectional SEM images of palates from all three groups were obtained to support MTV data. Results: The results indicate that ECIG-generated aerosol has a modest inhibitory effect (p<0.05) on MTV one day post-exposure (0.09±0.01) compared to control MTV (0.16±0.03 mm/sec mm/sec). In contrast, smoke completely inhibits MTV from 0.14±0.03 mm/sec immediately before exposure to 0.00 mm/sec immediately after exposure and the MTV is unable to recover one day later. SEM images of control palates and palates exposed to ECIG-generated aerosol both show cilia throughout their epithelial surface, while some areas of palates exposed to smoke are completely devoid of cilia. Additionally, the epithelial thickness of aerosol-exposed palates appears thicker than control palates while smoke-exposed palates appear to be thinner due to epithelial disruption. Conclusions: These results indicate that ECIG-generated aerosol has only a modest effect on mucocilary clearance of bullfrog palates and aerosol sedimentation accounts for epithelial thickening. In accordance with the primary literature, conventional cigarette smoke dramatically inhibits mucociliary clearance and is, in part, due to decreased number of cilia and disruption of the smoke-exposed epithelium.